Pemberdayaan Pecalang Desa Adat Sumerta dalam Penanggulangan Covid-19 - I Made Mardika; Ida Bagus Udayana Putra; A.A.G Oka Wisnumurti (Universitas Warmadewa, 2020)
Sumerta Traditional Village, located 4 KM east of the center of Denpasar City, seeks to participate in accelerating the handling of the Covid-19 Pandemic in its area. In accordance with the policy of the Governor of Bali, at the village / kelurahan level a Mutual Cooperation Task Force was formed based on the customary village. Through the Collaborative Task Force at the customary village level, Pecalang is at the forefront of preventing and overcoming the Covid-19 outbreak. All Sumerta Traditional Village pecalang are the main force in handling the Covid-19 pandemic. Even so, pecalang people do not know carefully the role that must be played in tackling and preventing the corona virus outbreak. In carrying out this humanitarian task, the pecalang must be supported by adequate facilities and infrastructure. In addition, basic necessities in the form of healthy food must also be available while they are carrying out their duties. Taking into account this phenomenon it is deemed necessary to do community service (PKM) to pecalang in Sumerta Traditional Village. This PKM targets community groups, especially the pecalang in Sumerta Traditional Village. Given that the pecalang is an organ of a traditional village, the PKM partner is Bendesa, the Sumerta Traditional Village. The problems faced by partners are: (1) the unknown role that pecalang can play in overcoming and preventing the covid-19 outbreak (2) lack of available facilities and infrastructure in carrying out epidemic prevention and control tasks, and (3) assistance for basic necessities obtained pecalang is not sufficient. This PKM aims to solve the problems faced by partners, namely counseling / mentoring the role of pecalang in tackling Covid-19, meeting the availability of materials for the prevention of the Covid-19 Pandemic in the form of masks and hand sanitizers, and providing basic food assistance to all pecalang in Sumerta Traditional Village. Thus this PKM uses two approaches, namely the method of mentoring / counseling, and service assistance to the pecalang. The two solutions offered are expected to increase the role of the pecalang in handling the Covid-19 pandemic, the availability of facilities for prevention / overcoming the outbreak and partners to obtain basic necessities for their household needs.